The Effectiveness of Cognitive-Behavioral Therapy on Perceived Stress in Adolescents with Social Anxiety Disorder - Alijani Baei, Tabassom; Mirzaian, Bahram; Norouzi, Asghar (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to investigate the effectiveness of cognitive-behavioral therapy (CBT) on perceived stress in adolescents with social anxiety disorder. Methods and Materials: The research method was quasi-experimental, utilizing a pre-test and post-test design with a control group, along with a one-month follow-up phase. The statistical population included all adolescents diagnosed with social anxiety disorder, attending 8 counseling centers in Babol, during spring 2024. Initially, the Connor Social Anxiety Questionnaire (2000) was distributed among all participants, and 30 individuals scoring between 16 and 25 (the cut-off score of the questionnaire) were selected using convenience sampling. These individuals were randomly assigned to experimental and control groups. Data were collected using the Perceived Stress Scale (Cohen, 1983) and the Connor Social Anxiety Scale (1969). The experimental group received cognitive-behavioral therapy based on Beck’s (1998) manual, administered in 12 sessions of 90 minutes each. The intervention was applied exclusively to the experimental group, while no intervention was provided to the control group. Data were analyzed using repeated measures analysis. Findings: The findings indicated a significant difference in the perceived stress scores between the experimental and control groups in adolescents with social anxiety disorder (P ≤ 0.01). In general, cognitive-behavioral therapy is effective in reducing perceived stress in adolescents with social anxiety disorder (P ≤ 0.01). Conclusion: Given the results of this study, the role of cognitive-behavioral therapy in creating changes in perceived stress holds important therapeutic implications.